Predicting global strain limits for corrugated panels. (1st January 2020) - Wang, C.; Xia, Y.; Friswell, M.I.; Saavedra Flores, E.I.
Abstract: Corrugated panels have many potential applications in civil, mechanical and aerospace engineering. The research on morphing aircraft requires the derivation of deformation limits of corrugated panels, which can be used as the constraint conditions for the design and optimisation of morphing structures. The relationship between the local and global strains of the equivalent models for corrugated panels is derived, which makes the prediction of the maximum strain available. Thus, from the maximum strain criterion, the global strain limit is evaluated under different load conditions. The results from the proposed analytical method are compared to those from detailed finite element models, which indicates a good agreement for all of the analysed cases. The influence of the geometric parameters of the corrugation shape is also investigated.